ICCAs as a Bio-Geo-Cultural Foundation for Strengthening the Aspiring Sangkulirang–Mangkalihat Geopark - Ronna Meila Leswana; Arzyana Sunkar; Sarwititi Sarwoprasodjo; Resti Meilani (Green Publisher Indonesia, 2026)
The Sangkulirang–Mangkalihat karst landscape in East Kalimantan possesses exceptional bio-geocultural value and has historically been safeguarded by the Dayak Basap Indigenous community. While Indigenous and Community Conserved Areas (ICCAs) and Geoparks both aim to promote sustainable land management, the synergistic integration of Indigenous spiritual-ecological practices within formal Geopark frameworks remains underexplored, particularly in tropical karst environments. To address this research gap, this study examined the integration of ICCAs within the Geopark framework to promote participatory conservation and responsible tourism. Employing a qualitative methodology comprising ethnographic fieldwork, in-depth interviews with Indigenous stakeholders, and field observations, this research evaluated traditional conservation mechanisms. The findings revealed that the traditional governance systems and cultural rituals of the Dayak Basap community maintained ecological and spiritual balance, reflecting the core principles of ICCAs. The study identified three specific ICCAs—Mengkuris Cave, Mount Kepang, and Kiamplasan—that uniquely integrated heritage, ecological, and community values. The integration of these frameworks demonstrated a strong complementary relationship; ICCAs provided social, cultural, and spiritual foundations, while Geoparks offered institutional recognition, technical support, and international networks to support sustainable geotourism. These findings provided important policy implications, suggesting that regional and national governments should formally incorporate ICCA recognition into Geopark zoning regulations to strengthen the legal protection of Indigenous governance systems. Ultimately, this synergy established a replicable model for responsible tourism that balances biodiversity conservation, cultural resilience, and equitable development, providing a critical framework for advancing global socio-ecological sustainability efforts.